Imovation in shaping dynamic capabilities of organisations = Imowacje w procesie kształtowania dynamicznych zdolności organizacji - Krzakiewicz, Kazimierz; Cyfert, Szymon (Zielona Góra: Faculty of Economics and Management Press)
The underlying assumption of the article is that imitation is as important as innovation when creating a long-term competitive advantage, and that a systematic, strategic approach to imitation is necessary to ensure efficient and effective innovation. Viewed in this light, imitation is a rare and complex dynamic capability which organisations should properly develop and skillfully use.
Keywords: zdolności organizacji; imowacje; innowacje; imitacje; dynamic capabilities; imovation; innovation; imitation